Punishment for the greater good - Kolber, Adam J. (Studies in penal theory and philosophy, 2024)
"If you or I locked someone in a room for years at a time, it would be a serious crime. Yet governments regularly confine people against their will. Why is it a vicious legal and moral wrong when you or I forcibly confine someone but generally lauded when the state locks up criminal offenders? Punishment theorists have struggled for centuries to give a satisfactory answer. When theorists try to answer, they usually address criminal justice under abstract, idealized conditions that assume away moral and empirical uncertainty. But we don't have time to wait for a perfect moral theory, and the history of philosophy suggests we will never find it"--